Construction of ecological security networks and the identification of priority areas for ecological restoration in Fujiang River Basin - Chen, Hao; Wang, Yingwei; Cheng, Zhongqi; Ma, Li (Frontiers in Environmental Science, 2025)
The construction of regional ecological security networks serves as an important strategy for improving the function of ecosystem services, identifying ecological restoration priority areas based on overall protection and systematic management is the main measure to promote the ecological restoration of national land space in a scientific and orderly manner. In this study, the Fujiang River Basin was taken as the study area, while the human footprint and landscape ecological risk model were used to quantitatively evaluate the negative interference of the ecosystem. The importance evaluation results of ecosystem services and the minimum cumulative resistance model were used to construct the ecological security network of the Fujiang River Basin with the ecological source as the “key patch,” the ecological corridor as the “axis”, and the ecological node as the “hub.” The key areas with high negative interference in the ecological network were extracted as the priority areas of ecological restoration and targeted restoration measures were proposed. The results showed that: (1) the importance of ecosystem services in the Fujiang River Basin could be comprehensively analyzed by selecting indicators such as water conservation, soil and water conservation, and habitat quality. The Conefor tool was used to evaluate the landscape connectivity of candidate source patches, where 23 ecological sources were extracted, an ecological source area of 7638.88 km2 was identified, which was clustered in the eastern margin of the Qinghai-Tibet Plateau and sporadically distributed in the parallel mountains of eastern Sichuan. (2) The ecological corridors in the study area were distributed in the “cobweb” pattern, with a total length of 2249.32 km, and 26 ecological nodes were scattered in the low-resistance area of the corridors. Based on the ecological network of sources and corridors forming networks, habitat connectivity, the ecological construction idea of one corridor and two areas was proposed. (3) Based on the spatial superposition of ecological security networks and negative interference surfaces, the priority areas of ecological restoration in the Fujiang River Basin were identified. Combined with the spatial distribution characteristics and typical problems of each priority area for ecological restoration, corresponding ecological restoration strategies were proposed to ensure connectivity between ecological sources and the integrity and stability of ecological networks. The above results could serve as a scientific reference for clarifying the ecological security pattern of the study area, improving the dynamic monitoring ability of ecologically fragile areas, and formulating targeted protection and restoration measures.